VISUAL IMAGING CAPACITY AND IMAGERY CONTROL IN FINE ARTS STUDENTS - Pérez-Fabello, Maria José; Campos, Alfredo; Gómez-Juncal, Rocío (Perceptual and motor skills, 2007)
This study investigated relationships between visual imaging abilities (imaging capacity and imagery control) and academic performance in 146 Fine Arts students (31 men, 115 women). Mean age was 22.3 yr. (SD= 1.9; range 20-26 yr.). All of the participants who volunteered for the experiment regularly attended classes and were first, second, or third year students. For evaluation of imaging abilities, the Spanish versions of the Gordon Test of Visual Imagery Control, the Vividness of Visual Imagery Questionnaire, the Verbalizer-Visualizer Questionnaire, and Betts' Questionnaire Upon Mental Imagery were used. Academic performance was assessed in four areas, Drawing, Painting, Sculpture, and Complementary Subjects, over a three-year period. The results indicate that imagery control was associated with academic performance in Fine Arts. These findings are discussed in the context of previous studies, and new lines of research are proposed.